P431 Early mucosal healing at week, 10 with ozanimod predicts clinical outcomes at week, 52: Post hoc analysis of the phase, 3 True North clinical trial. (21st January 2022) - Reinisch, W; Axelrad, J; Ahmad, H A; Pondel, M; Ather, S; Elegbe, A; Sninsky, C; Longman, R
Abstract: Background: Ozanimod, a sphingosine, 1-phosphate (S1P) receptor modulator selectively targeting S1P1 and S1P5, is approved in multiple countries for the treatment of relapsing multiple sclerosis and in the United States for the treatment of moderately to severely active Ulcerative Colitis (UC). A treat-to-target strategy for Inflammatory Bowel Disease (IBD) has been outlined in the Selecting Therapeutic Targets in IBD (STRIDE-II) consensus recommendations. Mucosal healing was identified as an important treatment target and may be associated with improved patient (pt) outcomes. Here we assess the relationship between early mucosal healing at week (wk), 10 and clinical outcomes at wk, 52 in ozanimod-treated pts with moderately to severely active UC in the phase, 3 True North trial (NCT02435992). Methods: A subset of pts in True North were randomised to and/or received oral ozanimod, 0.92 mg (equivalent to ozanimod HCl, 1 mg) during the, 10-wk induction period, achieved clinical response at wk, 10 and continued ozanimod during the maintenance period. For this post hoc analysis, we examined clinical remission, corticosteroid (CS)-free remission, and mucosal healing at wk, 52 in pts with versus without mucosal healing at wk, 10. Clinical remission was defined as rectal bleeding subscore = 0, stool frequency subscore ≤1 (and ≥1-point reduction from baseline), and mucosal endoscopy subscore (MES) ≤1 without friability. CS-free remission was defined as remission with no CS use for ≥12 wk. Mucosal healing was defined as MES ≤1 without friability and a Geboes score <2.0. Results: Demographics and disease characteristics were generally well balanced between ozanimod-treated pts with (n=44) and without (n=186) mucosal healing at wk, 10, albeit a higher proportion of pts without mucosal healing had prior biologic exposure. Higher proportions of ozanimod-treated pts who achieved mucosal healing at wk, 10 had clinical remission, CS-free remission, and mucosal healing at wk, 52 versus pts who did not achieve mucosal healing at wk, 10 (Figure ). Among the ozanimod-treated pts who did not achieve mucosal healing at wk, 10, 24.2% went on to achieve mucosal healing at wk 52. Conclusion: Using a novel, stringent definition for mucosal healing, which requires endoscopic improvement and histologic remission (Geboes <2.0), ozanimod-treated pts who achieved mucosal healing at wk, 10 had improved clinical, endoscopic, and histologic outcomes at wk, 52. A proportion of pts who did not reach mucosal healing at wk, 10 benefited from longer ozanimod treatment, achieving mucosal healing at wk 52.